A comparative study of the perceived importance of information technology to rural and urban youth - Fernandez, Rhodora
The fast spread of information technology in our society today is inevitable . This research is a comparative study of the perceived importance of information technology to rural and urban youth, to the youth that is prone to every lates fashion and innovation. this study would like to know the extent of familiarity of the youth to information technology, its helpfulness to their lives and their idea of how important these technologies are. Sixty-five (65) rural and seventy (70) urban students were chosen to be the respondents of this research. Results of the study show that urban youth are more familiar with information technology. Likewise, both rural and urban respondents answered that is indeed very helpful to them in school. On the other hand, even if they agree that inormation technology is very helpful to them, they do not consider it very important or see great need to acquire those technologies personally.